Genome wide association studies on seven yield‐related traits of 183 rice varieties in Bangladesh - Nilanjan Roy; Acramul Haque Kabir; Nourin Zahan; Shahba Tasmiya Mouna; Sakshar Chakravarty; Atif Hasan Rahman; Md. Shamsuzzoha Bayzid (Plant Direct)
Abstract Rice genetic diversity is regulated by multiple genes and is largely dependent on various environmental factors. Uncovering the genetic variations associated with the diversity in rice populations is the key to breed stable and high yielding rice varieties. We performed genome wide association studies (GWASs) on seven rice yielding traits (grain length, grain width, grain weight, panicle length, leaf length, leaf width, and leaf angle) based on a population of 183 rice landraces of Bangladesh. Our GWASs reveal various chromosomal regions and candidate genes that are associated with different traits in Bangladeshi rice varieties. Noteworthy was the recurrent implication of chromosome 10 in all three grain‐shape‐related traits (grain length, grain width, and grain weight), indicating its pivotal role in shaping rice grain morphology. Our study also underscores the involvement of transposon gene families across these three traits. For leaf related traits, chromosome 10 was found to harbor regions that are significantly associated with leaf length and leaf width. The results of these association studies support previous findings as well as provide additional insights into the genetic diversity of rice. This is the first known GWAS study on various yield‐related traits in the varieties of Oryza sativa available in Bangladesh—the fourth largest rice‐producing country. We believe this study will accelerate rice genetics research and breeding stable high‐yielding rice in Bangladesh.